The Concept of Literacy in the Qur'an, Surah Al-'Alaq, Verses 1-5 - Asep Sobirin; Hafid; Cecep Anwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research is an effort to examine the concept of literacy within the content of the Qur'an, Surah Al-'Alaq verses 1-5, based on the explanations of Tafsir scholars (Mufassir) and the views of previous researchers who have discussed the content of these verses using various approaches and different titles. This study employs a qualitative approach by applying a descriptive method, incorporating concepts and theories. From the results of this examination, it can be concluded that the content of the Qur'an in Surah Al-'Alaq verses 1-5 contains the concept of literacy, namely reading and writing. The first verse,